Dinâmica e lixiviação de sons em colunas de solo de uma área irrigada com água residuária - Follador, Franciele Aní Caovilla (2005)
This work evaluated the infiltration and leaching of ions processes in a soil cultivated with soybean when it was irrigated with wastewater origineted from the suinoculture (ARS). The experiment was carried out in greenhouse at the Agricultural Engineering Experimental Centre and at Hydraulics Laboratory, both belonging to the West Parana State University, and the last one, belonging to Hydrical Resources and Environmental Sanitation- RHESA, being the chemical analyses performed in the Soil Analysis Laboratory of Cascavel - PR. The soil from the experimental area is classified as Latossolo Vermelho distroférrico típico having very loamy texture, with 68% of clay, 13% of silte and 19% of sand. The ARS used was concentrated and utilized within the following levels: 0, 25, 50 and 75%, being performed the treatments T1, T2, T3 and T4, respectively and five repetitions. The culture used was the soybean (Glycine Max L. Merril), cultivar CD 216 from the Technological and Economical Development Agricultural Cooperative Ltda. (COODETEC).The soil samples were removed for performing the physical and chemical analysis in the depths of 20, 40 and 60 cm, to verify the íons movement in field. As soon as possible, the essays of infiltration speed were performed. In the sequence the undisturbed and disturbed soil columns were collected for performing the essays of leaching ion. The results allowed to conclude that there was no effect of the depth on the treatments, nor of the treatments about the depths, only for the element potassium and for the capacity of cationic exchange that the depth was significant. In relation to the speed of basic infiltration - VIB, was noticed a greater value for the treatment 1. About the results obtained with the disturbed columns, most parameters showed grater when applied T4, only for the nitrogen amoniacal it was verified the same values for all treatments. In relation to the CE was observed in the first point analyzed that the T2 was greater, however, starting from the second point analyzed the greater values obtained were for the T4. About the undisturbed columns, was noticed, in relation to the T4, larger values for the following parameters: P, K, and Nitrate. The nitrogen was larger for the T3, followed by the T4. For the nitrogen amoniacal, the behavior of the undisturbed column was the same as the disturbed one. The pH was larger for the T1, and the value was close for 7,0. The CE was larger for the T3, followed by the T4. It is concluded, therefore, that the T4 had influence in the two applied methodologies, so far too probably because of the amount of affluent applied.